Heterogeneous oxidation between the two surfaces of the Cu66Zr34 amorphous ribbon. (February 2022) - Liu, Binbin; Liu, Caiyun; Jiang, Xin; Zhang, Lei; You, Li; Zhen, Shuying; Liu, Zhiyuan; Ye, Feng
Abstract: The oxidation behavior of the Cu66 Zr34 metallic glass from room temperature to 400 °C is studied. Heterogeneous oxidation was observed on both the surface contacting with the rotating roller (RS) and the free surface (FS). The RS is oxidized faster than the FS, while the raised region has a quicker oxidation rate than the groove-like region on the RS. The different oxidation rates are attributed to the higher free volume content frozen in the amorphous ribbon during sample preparation. A "swell-crack-outward diffusion of Cu" oxidation mechanism is proposed to explain the oxidation behavior, particularly at a temperature below 200 °C. Highlights: Heterogeneous oxidation was observed in the Cu66 Zr34 MG below 400 °C. Oxidation rate of different regions is affected by the free volume content. The surface contacting with the roller is oxidized faster than the free surface. A "swell-crack-outward diffusion of Cu" oxidation mechanism is proposed.